Impact of resection margin status on recurrence and survival in pancreatic cancer surgery. Issue 8 (18th March 2019) - Tummers, W S; Groen, J V; Sibinga Mulder, B G; Farina-Sarasqueta, A; Morreau, J; Putter, H; van de Velde, C J; Vahrmeijer, A L; Bonsing, B A; Mieog, J S; Swijnenburg, R J
Abstract: Background: The prognosis of patients with pancreatic ductal adenocarcinoma (PDAC) is poor and selection of patients for surgery is challenging. This study examined the impact of a positive resection margin (R1) on locoregional recurrence (LRR) and overall survival (OS); and also aimed to identified tumour characteristics and/or technical factors associated with a positive resection margin in patients with PDAC. Methods: Patients scheduled for pancreatic resection for PDAC between 2006 and 2016 were identified from an institutional database. The effect of resection margin status, patient characteristics and tumour characteristics on LRR, distant metastasis and OS was assessed. Results: A total of 322 patients underwent pancreatectomy for PDAC. A positive resection (R1) margin was found in 129 patients (40·1 per cent); this was associated with decreased OS compared with that in patients with an R0 margin (median 15 (95 per cent c.i. 13 to 17) versus 22 months; P < 0·001). R1 status was associated with reduced time to LRR (median 16 versus 36 (not estimated, n.e.) months; P = 0·002). Disease recurrence patterns were similar in the R1 and R0 groups. Risk factors for early recurrence were tumour stage, positive lymph nodes (N1) and perineural invasion. Among 100 patients with N0 disease, R1 status was associated with shorter OS compared with R0 resection (median 17 (10 to 24) versus 45 (n.e.) months; P = 0·002), whereas R status was not related to OS in 222 patients with N1 disease (median 14 (12 to 16) versus 17 (15 to 19) months after R1 and R0 resection respectively; P = 0·068). Conclusion: Although pancreatic resection with a positive margin was associated with poor survival and early recurrence, particularly in patients with N1 disease, disease recurrence patterns were similar between R1 and R0 groups. Graphical Abstract: In pancreatic cancer surgery, R1 status is determined largely by tumour characteristics. Although R1 resection is a major contributor to reduced survival and early recurrence, overall recurrence patterns are similar after R0 and R1 resections. Finally, in patients with N0 disease, surgical factors affect R1 status. Tumour biology important